2007
DOI: 10.1063/1.2716868
|View full text |Cite
|
Sign up to set email alerts
|

Band gap and Schottky barrier heights of multiferroic BiFeO3

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
208
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(234 citation statements)
references
References 34 publications
24
208
2
Order By: Relevance
“…[4][5][6][7][8][9][10] The optical properties of BiFeO 3 (BFO) are also different from most of the perovskite ferroelectric due to its lower bandgap (2.6-2.9 eV) and conducting domain walls. 11,12 Clark and Robertson 13 predicted both direct and indirect bandgaps around 2.5 eV using band structure model, and afterward Ihlefeld et al 14 reported a direct-gap transition at 2.74 eV; however, recently we also found a direct bandgap of 2.55 eV at T ¼ 295 K, an indirect band edge at 2.67 eV. 5 Conventional photoelectric (PE) devices are based on two basic principles: first, the generation of electrical charge carriers in the active medium under the illumination of light; and second, separation and detection of photoinduced charge carriers by in-built asymmetric potential of p-n junction or Schottky junction or difference in work function between electrodes and semiconductor.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The optical properties of BiFeO 3 (BFO) are also different from most of the perovskite ferroelectric due to its lower bandgap (2.6-2.9 eV) and conducting domain walls. 11,12 Clark and Robertson 13 predicted both direct and indirect bandgaps around 2.5 eV using band structure model, and afterward Ihlefeld et al 14 reported a direct-gap transition at 2.74 eV; however, recently we also found a direct bandgap of 2.55 eV at T ¼ 295 K, an indirect band edge at 2.67 eV. 5 Conventional photoelectric (PE) devices are based on two basic principles: first, the generation of electrical charge carriers in the active medium under the illumination of light; and second, separation and detection of photoinduced charge carriers by in-built asymmetric potential of p-n junction or Schottky junction or difference in work function between electrodes and semiconductor.…”
mentioning
confidence: 99%
“…42 Apart from other smaller corrections, 40 this value assumes non-polar BiFeO 3 and a clean metal-semiconductor interface, both conditions not being satisfied in our case: the bound surface charges associated to a polarization pointing down inside the ferroelectric domains are expected to increase the barrier height for electrons injected from the Cr electrode, as indeed observed. In addition, measurements in air allow for adsorbates to act as screening charges and they also contribute to changes in the electronic potential.…”
mentioning
confidence: 77%
“…Whether the transition is a Mott transition or a band transition is unproven. Various theoretical models disagree: Vasquez et al [3] get an ab initio Mott transition; Clark et al [23] got a band transition to a semimetal from a screened exchange model.…”
Section: Resultsmentioning
confidence: 99%